Prayer in Johannine perspective: an analysis of prayer in the Farewell Discourse and 1 John - Adams, Scott Lewis (Neotestamentica, 2020)
Over the years, prayer passages within the Fourth Gospel and 1 John have been examined in detail apart from one another. This work seeks to analyse them in light of one another, particularly the prayer passages located within the Farewell Discourse (14:12-14; 15:7-8, 16; 16:23) and 1 John (3:21-22; 5:14-18). This article begins by exploring how the Farewell Discourse prescribes prayer as the means by which greater works will be performed and much fruit produced in Jesus’s physical absence. Then attention is given to demonstrating that the author of 1 John, dissatisfied with the prayer tradition in the Farewell Discourse, provides a nuanced account that focuses on how confidence in prayer relates to real-life, ethical scenarios within the community he addresses (3:11-24; 5:14-17). Finally, this article concludes by arguing that the discussion of prayer in 1 John 5:14-17 is more concerned with the preservation of the believing community than its numerical growth. Attention will be given to analysing the prerequisites, privileges and purposes of prayer in both documents in order to provide a more complete, nuanced profile of Johannine prayer. It is my distinct honour and privilege to dedicate this article to the great Johannine scholar, Dr Jan van der Watt.